CLINICAL AND ANATOMICAL BASIS OF PERICARDIAL PUNCTURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Pericardial puncture, a critical medical procedure, involves accessing the pericardial sac for therapeutic or diagnostic purposes. This article reviews the clinical and anatomical foundations of pericardial puncture, highlighting its significance, associated risks, and the importance of precise anatomical knowledge in performing this procedure safely.